2015
DOI: 10.17265/1934-7359/2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thermal Bridge Impact in a Hotel Building for the Eight Brazilian Bioclimatic Zones

Abstract: This article aims to present an analysis of the influence of thermal bridges on reinforced concrete structural systems regarding energy performance of the envelope of a commercial building located in the bioclimatic zones 1 to 8 in Brazil, using computer simulation. The method used to achieve this goal includes the following steps: (1) definition and configuration of the base case; (2) definition and configuration of the reference model; (3) optimization of energy modeling; (4) energy modeling and comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ge and Baba 6 found that the presence of a thermal bridge could cause an increase in the annual heat load by 38%-42%. Cunha et al 7 concluded that the energy consumption of buildings when considering a thermal bridge was 40% higher compared to buildings without taking the thermal bridge into account. Moreover, the share of additional energy use in buildings caused by thermal bridges was growing.…”
Section: Introductionmentioning
confidence: 99%
“…Ge and Baba 6 found that the presence of a thermal bridge could cause an increase in the annual heat load by 38%-42%. Cunha et al 7 concluded that the energy consumption of buildings when considering a thermal bridge was 40% higher compared to buildings without taking the thermal bridge into account. Moreover, the share of additional energy use in buildings caused by thermal bridges was growing.…”
Section: Introductionmentioning
confidence: 99%